Does drawing down the U.S. strategic petroleum reserve help stabilize oil prices? - Lutz Kilian; Xiaoqing Zhou (Goethe University Frankfurt, Center for Financial Studies (CFS), 2020)
We study the effects of releases from the U.S. Strategic Petroleum Reserve (SPR) within the context of fully specified models of the global oil market that explicitly allow for storage demand as well as unanticipated changes in the SPR. We show that historically SPR policy interventions, defined as sequences of exogenous SPR shocks during selected periods, have helped stabilize the price of oil. Their effect on the price of oil, however, has been modest. For example, the cumulative effect of the SPR releases after the invasion of Kuwait in 1990 was a reduction of 2/barrel in the real price of oil after 7 months. Whereas emergency drawdowns tend to lower the real price of oil, we find that exchanges tend to raise the real price of oil in the long run. We also provide a detailed analysis of the benefits of the 2018 White House proposal to sell off half of the SPR within the next decade. We show that the expected fiscal benefits of this plan are somewhat higher than the revenue of 16.6 billion dollars projected by the White House.
urn:nbn:de:hebis:30:3-558277
Keywords: Q38; Q43; E62; 330; SPR; crude oil; oil inventories; storage; expectations; policy intervention; fiscal policy